The Coordination and control of smart inverters utilizing Volt-VAr and Volt-Watt in low voltage networks, and opportunities for South Africa - Xavier, Ria (Stellenbosch : Stellenbosch University, 2022)
Thesis (MEng)--Stellenbosch University, 2022.